Metabolitos secundarios de especies de la familia Lauraceae con potencial uso cosmético para el mejoramiento, protección y preservación de la piel (2018)
In the country there is a great variety of species belonging to the Lauraceae family, which is one of the most biodiverse families of plants. These present a great potential in the search for active compounds for the development of cosmetic products. At the moment the compounds of natural origin have a high demand in the cosmetic industry, for their characteristics and the security they offer in their use, in comparison with those of synthetic origin. This review article deals with the cosmetic properties of this family, specifically, such as its antioxidant qualities, antibacterial, control pigmentation and anti-inflammatory function, in which biological activity is reported for extracts and secondary metabolites extracted from species of this family.